Clarity Requirements for Dragon Dance Competition Rules and Regulations from the Coaches' Perspective and Construction of the Association's Guidance System (Journal of Global Humanities and Social Sciences, 2025)
Dragon dance sport originated from ancient Chinese rituals such as rain-praying and deity-worshipping. Since the 1980s, it has gradually advanced toward standardization, competitiveness, marketization, and internationalization. Its competition rules have undergone multiple revisions (from the 1995 to 2011 editions), with supporting regulations for equipment and youth events. However, ambiguities remain in the recognition of rules and difficult movements among coaches, committees, and referees. Using the literature review method, practical method, and logical analysis method, this study analyzes the demand for clarity of rules and regulations from the coaches' perspective and identifies core issues: In terms of difficulty rules: vague movement trajectories, inconsistent recognition of combined difficulties, and the 2011 Edition rules lagging behind innovative difficulties; In terms of equipment rules: unclear weight standards for dragon heads, creating dilemmas for coaches in equipment selection; In terms of "conventional practices" in rules: lack of unified definitions for music requirements. Based on these findings, the study proposes the construction of three systems: (1) A competition difficulty standard system centered on releasing a dragon dance difficulty technology database and updating videos of innovative difficulties; (2) An event information notification system focusing on supplementing rule details, conducting online Q&A sessions, setting up an official website message board, and an event chief referee Q&A area; (3) An event committee Q&A system featuring synchronous display of deduction codes and rule-based interpretation and Q&A. This study aims to enhance the clarity of dragon dance competition rules and regulations and assist the Chinese Dragon and Lion Dance Association (CDLDA) in promoting the further standardization, normalization, and competitiveness of dragon dance sport.